Enhancing Knowledge Through Education on Cervical Cancer Awareness and Human Papillomavirus Vaccination Early on Using Counseling Methods and E-Booklets - Juwita, Linda; Prabasari, Ninda Ayu; Marcello, Steven Aldo (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
Adolescents have not been the target of reproductive health programs, resulting in a lack of knowledge and motivation regarding reproductive health. This situation leads to many cases of reproductive health issues among adolescents. Knowledge correlates with the attitude of adolescents toward cervical cancer prevention. A negative attitude towards reproductive health, especially cervical cancer, will not trigger preventive actions. This community service activity aims to enhance knowledge of cervical cancer and the Human Papillomavirus (HPV) vaccine among adolescents at SMA Pembangunan Jaya 2. The method used in this community service activity is Asset-Based Community Development (ABCD). The activity includes health education on cervical cancer and the HPV vaccine using counseling methods and an e-booklet. The media to deliver the material consists of an e-booklet and a counseling presentation through PowerPoint (PPT). The target group comprises 71 female students from the 10th and 11th grades at SMA Pembangunan Jaya 2. An evaluation was conducted to measure the activity's success in implementing this community service. The evaluation was done by providing a pre-test before the health education material was delivered and a post-test after the material was provided. The results of this community service show an increase in knowledge about cervical cancer and the HPV vaccine. The pre-test results showed that most participants had poor knowledge, and after the educational session, the post-test results indicated that most participants had good knowledge. This shows an improvement in the participants' knowledge about cervical cancer and HPV vaccination through counseling methods and e-booklets.